Reporting or argumentation: is there more to it than a linguistic problem? - Jelen, Bogomir (Geologija, 2003)
The contribution is a rational discussion on problematic thinking and linguistic representation in two papers. It is based on soft knowledge delineation as in computing and information Science and on the theory of scientific research. In both cases good and disciplined way of thinking is a crucial process. The difficulties of the stratigraphic parts of the papers are analysed and rectified by applying formal critical thinking. The analysis revealed the omission of acknowledging the language of Science in general. As a consequence, the seeking for knowledge which should be truthtropic, and the truthfulness function of the texts are not corroborated in the investigated stratigraphic texts.